2012
DOI: 10.2500/aap.2012.33.3607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory factors associated with negative oral food challenges

Abstract: Children 2 Oral food challenges (OFCs) are the recommended procedure to document the resolution of food allergy, 3,4 but they are time-consuming, difficult to perform, require resources, and expose the patient to the risk of a significant allergic reaction. Food-specific IgE (FSIgE) levels have been used to predict the outcome of OFC because FSIgE levels above certain cut points were found to be highly predictive of positive OFCs.5-10 However, FSIgE levels are less effective in identifying children who experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…This might be because a 10 day OIT protocol was used. We, as did Leonard et al, [47] used a 21 day protocol and also found significant protection in the OIT alone group. Importantly, we found that BF2+OIT produced greater and more persistent protection than OIT alone.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This might be because a 10 day OIT protocol was used. We, as did Leonard et al, [47] used a 21 day protocol and also found significant protection in the OIT alone group. Importantly, we found that BF2+OIT produced greater and more persistent protection than OIT alone.…”
Section: Discussionsupporting
confidence: 76%
“…Many previous studies found that OIT causes transient elevation of IgE in patients 47,48,49 and murine models. 30 Our study also found that OIT alone induced higher levels of IgE immediately after com- IL-10/IL-4 ratios have been associated with FA status, and a higher ratio was associated with food tolerance restoration in patients.…”
Section: Dna Methylation Levels At Il-4 Inf-c and Foxp3 Gene Promotersmentioning
confidence: 99%
“…Our results demonstrated that the variation in OFC results is mainly due to differences in total serum IgE levels. In fact, nonspecific or low‐affinity IgE suppresses specific IgE‐mediated activation of basophils in vitro , and total serum IgE levels reportedly affect the clinical severity or reactivity of patients with a milk , β‐lactam , or Hymenoptera venom allergy. Most previous studies indicate that older patients show increased total IgE levels , and the present study confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…Age is considered a critical confounding factor affecting OFC results , although the precise reason remains unknown. Furthermore, some studies have indicated that total IgE levels could influence the results of an OFC ; therefore, we aimed to determine whether total IgE levels might be a more suitable confounding factor to be controlled than age.…”
mentioning
confidence: 99%
“…A alergia a proteína do leite de vaca (APLV) é a alergia alimentar (AA) mais comum na infância, com uma prevalência de 2 a 3% nessa população (Bock, 1987;Host et al, 1990;Liu et al, 2010;Sicherer, 2011). É um significante problema de saúde pública pelo risco de reação grave potencialmente fatal (Bock et al, 2007) (Solé et al, 2008;Fiocchi et al, 2010;Chafen et al, 2010;Boyce et al, 2010, Kattan et al, 2011Beigelman et al, 2012).…”
Section: Alergia a Proteína Do Leite De Vacaunclassified